2007
DOI: 10.1088/0264-9381/24/19/s26
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for stochastic background searches using Virgo and LSC interferometers

Abstract: We consider the question of cross-correlation measurements using Virgo and the LSC Interferometers (LIGO Livingston, LIGO Hanford and GEO600) to search for a stochastic gravitational-wave background. We find that inclusion of Virgo into the network will substantially improve the sensitivity to correlations above 200 Hz if all detectors are operating at their design sensitivity. This is illustrated using a simulated isotropic stochastic background signal, generated with an astrophysically-motivated spectral sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…For any given real 4 IFOs it is necessary to compare these two optimal approaches of detecting the SGWB. Cella et al (2007) has shown that the approach of combining multiple pairs of IFOs using Virgo, LIGO and GEO can improve the detection ability to the SGWB by simulating an isotropic GW background with an astrophysically-motivated spectral shape. Fan & Zhu (2008) compared the detection ability of the two approaches for stochastic GWs from string cosmology.…”
Section: Introductionmentioning
confidence: 99%
“…For any given real 4 IFOs it is necessary to compare these two optimal approaches of detecting the SGWB. Cella et al (2007) has shown that the approach of combining multiple pairs of IFOs using Virgo, LIGO and GEO can improve the detection ability to the SGWB by simulating an isotropic GW background with an astrophysically-motivated spectral shape. Fan & Zhu (2008) compared the detection ability of the two approaches for stochastic GWs from string cosmology.…”
Section: Introductionmentioning
confidence: 99%
“…Additional searches of S4 LIGO data set limits on the strength of possible point-like backgrounds [115] and (by correlating LIGO Livingston data with data from the ALLEGRO bar detector) set a higher-frequency limit of Ω gw (915 Hz) < 1.02 [116]. Correlation measurements using LIGO and Virgo data are expected to improve the high-frequency measurement [117]. Further searches for anisotropic backgrounds are also being conducted.…”
Section: Search Resultsmentioning
confidence: 99%
“…With more than two instruments, there are multiple baselines and multiple calibration uncertainties to marginalize over. For instance, the stochastic background search using initial LIGO and Virgo data [6,7] involved 4 different instruments I ∈ {H1, H2, L1, V1} and 5 different baselines α ∈ {H1L1, H1V1, H2L1, H2V1, L1V1}.…”
Section: Calibration Uncertainty With Multiple Baselinesmentioning
confidence: 99%